Characteristics of diagenetic fluids affecting two major carbonate units on Victoria Island, Northwest Territories - Mathieu, Jordan-Paul (Laurentian University of Sudbury, 2014)
Diagenetic histories of Proterozoic and Paleozoic carbonate strata on Victoria Island, in the Canadian arctic, are poorly understood, and their potential to be associated with base metals or petroleum is unknown. Using fluid inclusion and geochemical techniques, it was determined that the diagenetic fluid compositions of two major carbonate units, the Wynniatt Formation and the “Victoria Island formation”, were largely controlled by fluid-rock reactions in reservoirs and by mixing of multiple fluids. Diagenesis of the Wynniatt Formation resulted from the progression from a shale-dominant fluid mixture to a meteoric-dominant mixture. Fluid composition of “Victoria Island formation” was a shale-dominant mixture. A change in fluid:rock from low to high was recorded during diagenesis of both units. Metals and hydrocarbons transported to the study sites were ac-quired by the fluids during interaction with the respective source reservoirs. Mixing of diagenetic fluids follows the established ‘mixing model’ used to explain many other min-eralised locations. The diagenetic fluids that affected the strata in this study were compa-rable to those that produced the Polaris Zn-Pb deposit. This similarity suggests that there is potential for mineralisation on Victoria Island. Master of Science (MSc) in Geology